Factors Affecting Activity of Cellulose Enzymes Produced By Three Fungi - Abdel-Rahim, Awad M.; A. Elmustafa, Amina (Gezira Journal of Engineering and Applied Sciences, 2014)
Three fungi (Trichoderma viride, Asperigillus niger and Penicillium digitatum) were used in the present study for the production of the cellulase enzymes (carboxymethylcellulase and cellobiase). The effects of different metal ions on the activities of these enzymes were , caused a ++and Mn+ , K++, Ba++using the reducing group method. The addition of Ca investigatedsignificantly higher increase in the activity of the carboxymethylcellulase enzyme of the three . However, the addition ++and Zn++ e a less increase was found by the addition of Mgfungi, whilactivity. The activity of the is enzyme caused a decrease in th ++, and Fe++, Cu++, Cd+, Ag+of Naand +ence of Hg, but it was decreased in the pres+and K ++cellobiase was increased with Caat the was occurred A. nigerenzyme produced by cellobiasehe higher activity of the T.++Cd, however, ++Ca and ++900 ppm for Mn –500 , while it occurred at+900 ppm of K –200 of range P. and T. viride ase of bothobiFor the cell 900 ppm. –800 of at the range it occurred ,++Ba for . ++, no significant different was noticed with different concentrations of Cadigitatum fungi at all th ase enzyme of boobigave a lower activity for the cell ++On the other hand, Ba concentrations. The optimum temperature for the carboxymethylcellulase enzyme activity was at . P. digitatum and T. viride bothfor C 050 –C 0it was between 40 , whileA. niger50°C for C.0However, the optimum temperature for the cellobiase activity of the three fungi was at 40 The optimum activity of the carboxymethylcellulase enzyme produced by A. niger was at pH 4, and for that of T. viride was at pH 6. Two peaks were detected for the same enzyme produced by P. digitatum, at pH 6 and pH 7. However, the optimum pH value for the cellobiase enzymes produced by the three fungi was at pH 4.0 only.